Prediction of potential distributions of Morina kokonorica and Morina chinensis in China - Qing Yuan; Jingjing Zhang; Zhiwen Yao; Quan Zhou; Penghui Liu; Wenhui Liu; Hairui Liu (Ecology and Evolution, 2024)
Abstract Changes in the habitats of species can provide insights into the impact of climate change on their habitats. Species in the genus Morina (Morinoideae) are perennial herbaceous plants that are mainly distributed in the South Asian Mountains and Eastern Mediterranean. In China, there are four species and two varieties of this genus distributed across the Yunnan, Sichuan, Qinghai, and Gansu provinces. This study used the optimal MaxEnt model to simulate past, current, and future potentially suitable habitats of Morina kokonorica and Morina chinensis. Seventy data of M. kokonorica occurrences and 3 of M. chinensis were used in the model to predict potentially suitable habitats. The model prediction results indicated that both M. kokonorica and M. chinensis exhibited trends of northward migration to higher latitudes and westward migration along the Himalayas to higher elevations, suggesting that the northern valleys of Hengduan Mountains and northern and eastern parts of the Himalayas were potential refugia for M. kokonorica, and the potential refugia for M. chinensis was located in the eastern part of Qinghai‐Tibet Plateau. The results of this niche analysis showed that the two species had higher levels of interspecific competition and that the environmental adaptability of M. chinensis was stronger. This research could help further understand the response pattern of Morina to environmental change, to understand the adaptability of species to the environment, and promote the protection of species.